From the terror to the hope: Places of memory in Navarre - Gastón Aguas, José Miguel; Layana Ilundain, César (Huarte de San Juan. Geografía e Historia, 2020)
The political cleaning triggered by the rebels in July 1936 caused a unprecedented wave of violence in Navarre, among whose demonstrations stresses the murder of thousands of people; murders that almost always where extrajudicial and finished, also, with the clandestine burial of the bodies. It is intended to contrast this conscious policy of concealment and erasure of all traces of these people with the existence of a resistant memory during the Francoism, which emerged in the Transition with the early exhumations. Likewise, draw from the concept of places with historical memory, understanded as a relevant space for the memorial heritage, the public politics applied at the development of the Foral Law 29/2018 are being analysed, of places with historical memory of Navarre, that have tried to start from the previous initiatives of the families and associations and link with them.